Biohydrogen production from wastes of plant and animal origin via dark fermentation - Weronika Cieciura-Włoch; Sebastian Borowski (Journal of Environmental Engineering and Landscape Management, 2019)
This study investigated the batch experiments on biohydrogen production from wastes of plant and animal origin. Several substrates including sugar beet pulp (SBP), sugar beet leaves (SBL), sugar beet stillage (SBS), rye stillage (RS), maize silage (MS), fruit and vegetable waste (FVW), kitchen waste (KW) and slaughterhouse waste (SHW) including intestinal wastes, meat tissue, post flotation sludge were tested for their suitability for hydrogen production. Generally, the substrates of plant origin were found to be appropriate for dark fermentation, and the highest hydrogen yield of 280 dm3 H2/kg VS was obtained from fruit and vegetable waste. Contrary to these findings, slaughterhouse waste as well as kitchen waste turned out to be unsuitable for hydrogen production although their methane potential was high. It was also concluded that the combined thermal pretreatment with substrate acidification was needed to achieve high hydrogen yields from wastes.